Sailing as a family tourism in the opinion of sailing club members Charzykowo Chojnice - Bartosz Błażejczak; Marek Napierała; Rafał Gotowski (Kazimierz Wielki University, 2017)
The aim of this study was to find an answer to the question: what prompted the respondents to sailing. To get an answer to the question diagnostic survey method was used, and the research technique was used for the survey. The study was conducted among a total of 100 sailors (30 girls and 70 boys). Conclusions: (1) The subjects of the sport of sailing knowledge derive from the family, (2) Family traditions influence the choice of sailing discipline (3) The girls like the boys prefer active leisure model, (4) Both boys and girls all his free time spend on an adventure with the club.